A novel Asp380Ala mutation in the GLC1A/myocilin gene in a family with juvenile onset primary open angle glaucoma. Issue 11 (November 1998) - Kennan, A M; Mansergh, F C; Fingert, J H; Clark, T; Ayuso, C; Kenna, P F; Humphries, P; Farrar, G J
Abstract : Glaucoma describes a clinically and genetically heterogeneous group of diseases that result in optic neuropathy and progressive loss of visual fields. A gene for juvenile onset primary open angle glaucoma JOAG) has recently been mapped to 1q21-31. Mutations in the trabecular meshwork induced glucocorticoid response gene (TIGR, also known as myocilin or the GLC1A locus) have been found to cause both juvenile and later onset primary open angle glaucoma. Family TCD-POAG1 is a Spanish kindred, which segregates JOAG in an autosomal dominant fashion. This family was found to be linked to the previously identified GLC1A locus on chromosome 1q. Direct sequencing of the TIGR/myocilin gene showed a heterozygous A to C transition in codon 380, resulting in the substitution of alanine for aspartic acid (Asp380Ala). This substitution created a StyI restriction site, which segregated with the JOAG phenotype and permitted rapid screening of all members of the family. This restriction site was not present in 60 controls.